Pengaruh Keterikatan Kerja dan Dukungan Rekan Kerja terhadap Kinerja Tugas - Farah Putri Wenang Lusianingrum; Lina Affifatusholihah; Fadhilah Fadhilah (Politeknik Negeri Bengkalis, 2020)
This study tries to explain the antecedents of task performance using Self Determination Theory from autonomy and relatedness elements that are often ignored in the work environment. The autonomy element is represented by work engagement and the relatedness element is represented by the coworker support. The purpose of the study was to examine the effect of work engagement and coworker support on task performance. Thus, quantitative research methods were chosen because according with the research objectives. Yogyakarta Provincial Government employees who have worked for 2 years as many as 150 people are respondents in this study. The results of the study prove that work engagement and coworker support contribute to the improvement of employee task performance.